The organizationalculture of the heads of sports clubs in Diyala and its relationship with the administrative control authority - Mahmoud ShahdH, Osman (International Journal of Psychosocial Rehabilitation, 2020)
For the purpose of identifying the organizational culture of the presidents of sports clubs in Diyala and its relationship with the administrative control authority, the researcher used the method of description in the style of correlation relations on a sample of 63% members selected in a deliberate manner. After distributing the tools of research on them and collecting data and processing statistically to obtain the desired results, the researcher reached the most important conclusions: there is a moral correlation between the organizational culture and the administrative control authority and its dimensions with the presidents of sports clubs in Diyala. The researcher recommends further research on modern administrative understanding and its relationship to the administrative control authority or other variables concerning the administrative aspects of the presidents and members of the central sports federations and provinces.